2017
DOI: 10.1109/tnsre.2016.2631446
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Control of Cortical Pyramidal Neurons With Micromagnetic Stimulation

Abstract: Magnetic stimulation is less sensitive to the inflammatory reactions that plague conventional electrode-based cortical implants and therefore may be useful as a next-generation (implanted) cortical prosthetic. The fields arising from micro-coils are quite small however and thus, their ability to modulate cortical activity must first be established. Here, we show that layer V pyramidal neurons (PNs) can be strongly activated by micro-coil stimulation and further, the asymmetric fields arising from such coils do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
68
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(73 citation statements)
references
References 49 publications
5
68
0
Order By: Relevance
“…In the in vivo experiments, it was demonstrated that μMS of the DCN resulted in the generation of neuronal activities in the IC and in the cochlea. The in vivo experiments have recently been extended to the feline cochlea ( Lee and Fried, 2017 ). Hence, μMS can elicit neuronal activation within an interconnected neural circuit and is not restricted to modulation of only local circuitry.…”
Section: Resultsmentioning
confidence: 99%
“…In the in vivo experiments, it was demonstrated that μMS of the DCN resulted in the generation of neuronal activities in the IC and in the cochlea. The in vivo experiments have recently been extended to the feline cochlea ( Lee and Fried, 2017 ). Hence, μMS can elicit neuronal activation within an interconnected neural circuit and is not restricted to modulation of only local circuitry.…”
Section: Resultsmentioning
confidence: 99%
“…This capacitance was also shown by the fact that dendritic activation needed longer rTMS trains (i.e. more energy), but when they are eventually activated, they fired with higher amplitudes and for a longer period after stimulation ceases (Lee and Fried 2017). A similar effect was shown in single neurons where current injection into dendrites furthest from the soma produced longer and larger action potentials compared to somatic current injection (Larkum et al 2007), especially in response to higher frequency and longer pulse width stimulation (Ledergerber and Larkum 2010).…”
Section: Discussionmentioning
confidence: 84%
“…Implantable magnetic stimulation was recently suggested and studied for its feasibility in in vitro 18 and in vivo 20 conditions, suppression of subthalamic nucleus activity 19 , eliciting neural activities of cortical pyramidal neurons 22 , and development of penetrating-type stimulating microcoils 2 . Although neuromodulation effects using coils developed by each research team have been extensively studied, there has been little research on the heat generated around the coil during magnetic stimulation.…”
Section: Discussionmentioning
confidence: 99%
“…The temperature rise did not significantly modulate synaptic activities in the hippocampal slice. In the future, the molecular and cellular mechanisms of CMS need to be further investigated using methods such as a western blotting 60 or immunohistochemistry 61 , 62 to analyze the variation of crucial proteins for synaptic LTD; calcium imaging 63 to confirm calcium signaling in network-level; Terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) to detect possible cell depth 64 , 65 ; patch-clamp recording using various receptor blockers 22 , 29 , 31 ; input-output curve for analyzing basal synaptic transmission 44 ; paired-pulse ratio to measure the short-term plasticity in the presynaptic terminal. Also, more experimental studies using various combinations of CMS parameters such as pulse width, ISI, ITI and duration of stimulation are desired.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation